Blood Supply Management During COVID-19 Pandemic and Ramadhan Fasting at a Tertiary Hospital - Teguh Triyono; Usi Sukorini; Rukmono Siswishanto (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
The worldwide pandemic of Coronavirus Disease 2019 (COVID-19) has a major implication for blood donation. The beginning of the pandemic occurred at the same time as Ramadhan fasting. This study aimed to evaluate blood donation, blood use trends, and several factors associated with the need for transfusion during the COVID-19 pandemic and Ramadhan fasting in Dr. Sardjito General Hospital (SGH). Information on blood donation and the use of blood components in the SGH-Blood Centre (SGH-BC) from 1 February to 30 September 2019 and 2020 were collected and analyzed. The average number of blood donations from February to September 2020 declined by 11.22% compared to the previous year. The average use of blood components from February to May 2020 also declined compared to the previous year. the decline found in this study was Packed Red Cells (PRC) by 15.43%; Thrombocyte Concentrate (TC) by 23.03%; Whole Blood (WB) by 73.64%; Fresh Frozen Plasma (FFP) by 10.56%; and Thrombocyte Apheresis (TA) by 32.87%. Two characteristics of donors remain unchanged between 2019 and 2020. Most of them were males and age younger than 25 years old. However, there was a shifting characteristic of donors in blood group, weight, and hemoglobin level. Declined number of blood donations might be caused by the pandemic situation and Ramadhan fasting. Blood usage also decreased in the early of this pandemic. The SGH-BC had modified some strategies to increase blood donation and decrease blood component use in this situation.